PENGARUH KEPEMIMPINAN, MOTIVASI DAN LINGKUNGAN KERJA FISIK TERHADAP KINERJA PEGAWAI NEGERI SIPIL - Gunawan, Bryan Adi; Damayanti, Damayanti (Sekolah Tinggi Ilmu Ekonomi Jayakarta, 2024)
Normal worker performance is the end result of certain movements completed with the aid of personnel in their paintings. If the effects of the paintings are in accordance with the requirements present in the affiliation, then the association's dreams may be done. The reason of this studies is to decide the have an impact on of management, motivation and physical paintings environment on worker performance on the Dinas Perindsutrian dan Tenaga Kerja Rembang Regency. The research become directed the usage of a saturated sampling approach so that 44 respondents were obtained. The information collection procedure uses a questionnaire. The facts evaluation method uses a couple of linear regression evaluation. The check used is a willpower test, which specially assessments how a good deal impact the existing independent variable factors have on the structured variable. The effects of this studies display that management has a mere fine effect, motivation has a huge advantageous impact, and the bodily work surroundings has a trifling fantastic impact on authorities overall performance.